Board of directors' effectiveness and operational risk disclosure on Indonesian Islamic bank performance: The mediating effect of sharia supervisory board quality - Yulianti, Yulianti; Haribowo, Ismawati (Universitas Negeri Surabaya, 2024)
Islamic banks today offer several financial and investment options. Despite being designated as a